PELATIHAN SINEMATOGRAFI UNTUK MENDUKUNG MEDIA PROMOSI UMKM AZOLLA - Ayu Wiwid Sintowoko, Dyah (Jurnal Abdimas Musi Charitas, 2023)
This training aims to make villagers, especially Azolla MSME owners, aware regarding theimportance of visual media as promotion tool. This activity was carried out to encourage UMKMAzolla in Kajen, Klaten Regency in responding to the mushrooming use of films with acinematographic approach in the current era. This is used to support the promotion of MSMEsin remote areas so they can survive in today's all-IT conditions. Moreover, currently thegovernment is clearly pushing creative economic policies, such as the presence of MSMEs. Themethod used is the pbased practice method, which is making promotional video works to developAzolla MSMEs. This film-based video (cinematography) may be made to boost promotion oflocal MSMEs so that it can be useful for various things, such as: (1) the independence ofMSMEs in promoting Azolla products; and (2) training the community's technological andvisual abilities. Therefore, empowering film skills, especially regarding cinematography, forlocal MSMEs really needs to be done. The results of this Community Service showed thatcreative strategies, especially in the audio-visual field, are still required to enhance the quality ofAzolla's MSME promotions. With cinematography, these MSMEs have higher opportunity todocument all their activities so the audio-visual documentation can be disseminated to socialmedia networks. However, continued community service is still very much needed.